Engineered cellulose nanocrystals-based cement mortar from office paper waste: Flow, strength, microstructure, and thermal properties. (1st July 2022) - Nasir, Muhammad; Aziz, Muhammad Arif; Zubair, Mukarram; Ashraf, Noman; Hussein, Tag Nasreldin; Allubli, Moath Khalid; Manzar, Mohammad Saood; Al-Kutti, Walid; A. Al-Harthi, Mamdouh
Abstract: In this study, three types of cellulose nanocrystals (CNCs), termed as C1, C2 or C3, of varied crystallinity (79.91–89.31%), diameters (0.1–1 μm), lengths (0.8–10 μm) and synthesized at solid to acid ratios (1g:20 ml to 1g:25 ml) were incorporated as a green additive (0–1.5% by wt. of cement) in the preparation of mortar. The performance of the developed mortar was examined by evaluating flow, compressive and flexural strengths, the volume of permeable voids, and thermal conductivity. The results were supported by XRD, FTIR, and SEM-EDX analyses. The C1 (synthesized with mild acid hydrolysis conditions) based mortar outperformed C2 (synthesized with harsh acid hydrolysis conditions having moderate crystallinity) and C3 (synthesized with harsh acid hydrolysis conditions having high crystallinity) based mortars. In general, the flow of mortar dropped linearly with the addition of CNCs due to agglomeration, depending on their particle sizes. The maximum compressive and flexural strengths, thermal conductivity, and minimum volume of voids recorded in C1 specimens were 34 MPa, 4.1 MPa, 0.96 W/mK, and 13.4%, respectively. These values were 21.7%, 28.1%, 17.1% higher, and 14.6% lower than that obtained in CNC-free mortar specimens, respectively. The enhanced performance of C1 specimens was attributed to more precipitation of –OH groups, strong Si–O-T chains, increased crystallinity of the products, and the intertwining of major elements in the cementitious composites. It also imparted crack-bridging effects leading to microstructural densification. It is postulated that the engineered C1 mortar has significant potential as an additive in construction applications from ecological, economic, and technical means. Highlights: CNCs derived from OPW with varying properties were used as green additive in mortar. CNCs synthesized with mild acid hydrolysis outperformed those with harsh conditions or high crystallinity. The optimum dosage of all three CNCs was 0.75 wt% of cement, regardless of synthesis technique. The mortar prepared with optimum type of CNCs exhibited up to 28% improvement in their properties. CNCs imparted crack-bridging and pore-filling effects leading to dense skeletal mortar matrix.